Kecerdasan Spiritual: Signifikansi dan Strategi Pengembangan - Naim, Ngainun (Institut Agama Islam Negeri (IAIN) Tulungagung, 2014)
Spirituality plays importance role to human life. This is due the existence of human being is of physical aspect only but also of spiritual aspect. Well managed spirituality will develop into spiritual quotient by which human being becomes intellectually, socially, and spiritually smart. In other words, well managed spirituality causes betterment in human life.